2012
DOI: 10.1186/1742-2094-9-1
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immunity in multiple sclerosis white matter lesions: expression of natural cytotoxicity triggering receptor 1 (NCR1)

Abstract: BackgroundPathogenic or regulatory effects of natural killer (NK) cells are implicated in many autoimmune diseases, but evidence in multiple sclerosis (MS) and its murine models remains equivocal. In an effort to illuminate this, we have here analysed expression of the prototypic NK cell marker, NCR1 (natural cytotoxicity triggering receptor; NKp46; CD335), an activating receptor expressed by virtually all NK cells and therefore considered a pan-marker for NK cells. The only definitive ligand of NCR1 is influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
93
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(99 citation statements)
references
References 51 publications
6
93
0
Order By: Relevance
“…Tollip was shown to facilitate the transport of polyQ protein aggregates to late endosome and protect neuronal cells from death (Oguro et al, 2011). Further supporting the role of Tollip in the pathogenesis of human Alzheimer's disease, a recent study reported that Tollip expression was significantly reduced in human brain samples collected from aged and Alzheimer's individuals as compared to young individuals (Cribbs et al, 2012). Based on these findings, we aim to examine the causal connection between Tollip deficiency and neurodegeneration in vivo by employing the Tollip deficient mouse model.…”
Section: Introductionmentioning
confidence: 86%
“…Tollip was shown to facilitate the transport of polyQ protein aggregates to late endosome and protect neuronal cells from death (Oguro et al, 2011). Further supporting the role of Tollip in the pathogenesis of human Alzheimer's disease, a recent study reported that Tollip expression was significantly reduced in human brain samples collected from aged and Alzheimer's individuals as compared to young individuals (Cribbs et al, 2012). Based on these findings, we aim to examine the causal connection between Tollip deficiency and neurodegeneration in vivo by employing the Tollip deficient mouse model.…”
Section: Introductionmentioning
confidence: 86%
“…Our phenotyping results suggest that other activating receptors, such as NKp46, could also contribute to CD4 T cell-mediated cytotoxicity, although the cognate ligand remains unknown. Interestingly, NKp46 was detected on lymphoid cells in demyelinated areas, especially in active MS lesions, but colabeling has not been performed to confirm whether these cells are NK cells or T cells (38). Finally, analysis of a small subset of donors (data not shown) suggests that NKG2C + CD4 T cells are mainly effector memory cells, being CCR7…”
Section: Discussionmentioning
confidence: 99%
“…Maternal inflammatory factors, such as interleukins, may directly or indirectly alter offspring neuronal progenitors and/or microglia, a myeloid-derived class of cells in the brain (McAllister and Patterson, 2012). These maternal factors act as important mediators of embryonic brain changes; elevated maternal interleukins have been demonstrated to alter offspring behavioral and brain outcomes in animal models; specific cytokines during pregnancy have been associated with offspring neuropsychiatric disorders such as autism spectrum disorder and schizophrenia (Petitto et al, 1997; Gilmore et al, 2004; Meyer et al, 2007; Ponzio et al, 2007; AL-Ayadhi and Mostafa, 2012). …”
Section: Introductionmentioning
confidence: 99%